1995
DOI: 10.1111/j.1476-5381.1995.tb15936.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of morphine on the nerve terminal impulse and transmitter release from sympathetic varicosities innervating the mouse vas deferens

Abstract: 1 The effect of morphine on both the propagation of the nerve terminal impulse along the sympathetic varicose axons as well as the evoked and spontaneous transmitter release has been evaluated.2 Morphine (1 yM) did not significantly change the shape or the regularity by which the nerve terminal impulse was recorded while evoked transmitter release was greatly reduced. 3 Morphine induced a uniform decrease in evoked transmitter release irrespective of the release probability of individual varicosities of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 30 publications
2
12
0
Order By: Relevance
“…An interesting difference between the opioid and cannabinoid systems lies in the response to their respective selective antagonists. Whereas naloxone alone does not normally affect the control contractile responses to electrical stimulation and produces no change in quantal release of neurotransmitter (Lavidis 1995), the selective CB 1 -receptor antagonist, SR141716A, has been shown previously to cause a small but significant increase in the twitch response at low frequency stimulation and a corresponding increase in ACh release compared with controls when measured in the presence Fig. 4.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…An interesting difference between the opioid and cannabinoid systems lies in the response to their respective selective antagonists. Whereas naloxone alone does not normally affect the control contractile responses to electrical stimulation and produces no change in quantal release of neurotransmitter (Lavidis 1995), the selective CB 1 -receptor antagonist, SR141716A, has been shown previously to cause a small but significant increase in the twitch response at low frequency stimulation and a corresponding increase in ACh release compared with controls when measured in the presence Fig. 4.…”
Section: Discussionmentioning
confidence: 96%
“…At the neuromuscular junction of the mouse vas deferens, where neurotransmission is sensitive to inhibition by opioids and cannabinoids Lavidis 1995), it has been suggested that procedures that lead to an increase in intracellular calcium concentration following nerve stimulation diminish the ability of morphine to lower transmitter release. Therefore in the present experiments, effects of (+)-WIN 55212 on the twitch response of the myenteric plexus preparation were compared with those of the µ opioid receptor agonist, normorphine.…”
Section: Introductionmentioning
confidence: 99%
“…The volume of solution injected sub-cutaneously was kept constant at 0.1 ml. On the 8th or 9th day animals were injected with a dose of saline (control) (1995) 116, 2860 -2865 Preparation of tissues See the methods section of the previous paper (Lavidis, 1995). The preparation was continuously perfused at a rate of 3 ml per minute with a modified Tyrode solution of the following composition (mM): NaCl 123.4, KCI 4.7, MgCl2 1.0, NaH2PO4 1.3, NaHCO3 16.3, CaCl2 1.0-8.0, glucose 7.8 and morphine 0.001.…”
Section: Treatment Of Animalsmentioning
confidence: 99%
“…is reduced when the extracellular calcium concentration is raised (Bennett & Lavidis, 1980;Illes et al, 1980). Extracellular recordings of the nerve terminal impulse (NTI) and excitatory junction currents (ej.cs) have demonstrated that morphine decreases transmitter release from sympathetic varicosities without affecting the propagation of the nerve impulse along terminal branches (Cunnane & Evans, 1988;Lavidis, 1995). This inhibitory affect of morphine on transmitter release can be reduced by procedures that are thought to increase the intracellular calcium concentration during nerve stimulation such as increasing the extracellular calcium concentration, during trains of nerve impulses and increasing the duration of the action potential with 4-aminopyridine (Lavidis, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation